Inteligencia emocional y pensamiento crtico en estudiantes del tercer grado de secundaria de una Institucin Educativa Experimental, Trujillo - 2020 - Moreto Guevara, Angie Vanessa (2022)
The current research is entitled The relationship between emotional intelligence and critical thinking in third secondary grade students of an experimental school, Trujillo 2020. This research work aims to determinate the relationship between emotional intelligence and critical thinking, in the academic area of citizenship, in third grade students of the school Rafael Narvez Cadenillas._x000D_ To do this, we used the quantitative statical method and the technique of the survey.The instruments used were a test and a questionnaire to measure the emotional intelligence and the critical thinking, respectively. The test that measures the emotional intelligence contained 25 items and the questionnaire that measures the critical thinking contained 30 items._x000D_ The results obtained through implementation of the instruments allowed us to know about the regular level of use and development of both the critical thinking skills and the emotional intelligence skills in the surveyed students. So also, the Pearson's rank correlation coefficient was used to measure the degree of correlation between the research variables, obtaining as a result the existence of a high correlation between emotional intelligence and critical thinking with a correlation coefficient of 0.977.